POTENSI LIMBAH TERNAK RUMINANSIA DI KABUPATEN SIDRAP - Purnomo, Nurul; M., Armayani (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2021)
Increasing livestock population has an impact on increasing livestock waste production. Livestock waste can be a source of environmental pollution but can also be processed into organic fertilizer and biogas. But until now there has been no research into waste production and the distribution of ruminant livestock waste production in Sidrap Regency. This study aims to determine the production of ruminant livestock waste and the distribution of livestock waste production in Sidrap Regency. The results showed that ruminant livestock waste production in Sidrap District reached 204,903 tons / year consisting of 235,797 tons / year of cattle livestock waste, 17,290 tons / year of buffalo and 1,816 tons / year of goats. Livestock waste production is spread throughout the entire district area. The highest livestock waste production in Pituriase District, amounting to 84,274 tons / year, then Watang Pulu District 78,235 tons / year, Panca Lautang 27,186 tons / year, Kulo 12,164 tons / year, Pitu Riawa 10.765 tons / year, Maritengae 9,867 tons / year, Panca Lautang 27,186 tons / year, Kulo 12,164 tons / year, Pitu Riawa 10.765 tons / year, Maritengae 9,867 tons / year, Panca Lautang Rijang 9,120 tons / year, Watang Sidenreng 8,407 tons / year, Tellu Limpoe 7,624 tons / year, Two Pitue 5,023 tons / year and Baranti 2,238 tons / year. Based on the results of the study, it can be concluded that the production of livestock waste in Sidrap Regency reaches 204,903 tons / year and is spread unevenly throughout the district.